Demulsification of Water in Iraqi Crude Oil Emulsion (Journal of Engineering, 2019)
Formation of emulsions during oil production is a costly problem, and decreased water content in emulsions leads to increases productivity and reduces the potential for pipeline corrosion and equipment used. The chemical demulsification process of crude oil emulsions is one of the methods used for reducing water content. The demulsifier presence causes the film layer between water droplets and the crude oil emulsion that to become unstable, leading to the accelerated of water coalescence. This research was performed to study the performance of a chemical demulsifier Chimec2439 (commercial) a blend of non-ionic oil-soluble surfactants. The crude oils used in these experiments were Basrah and Kirkuk Iraqi crude oil. These experimental work were done using different water to oil ratio. The study investigated the factors that have a role in demulsification processes such as the concentration of demulsifier, water content, salinity, pH, and asphaltene content. The results showed in measuring the droplet size distribution, in Basrah crude oil, that the average water droplet size was between (5.5–7.5) μm in the water content 25% while was between (3.3-4) μm in the water content 7%. The average water droplet size depends on the water content, and droplet size reduced when the water content of emulsion was less than 25%. In Kirkuk crude oil, in water content of 7%, it was between (4.5-6) μm, while in 20%, it was between (4-8) μm, and in 25% it was between (5-8.8) μm. It was found that the rate of separation increases with increasing concentration of demulsifier. For Basrah crude oil at 400ppm the separation was 83%, and for Kirkuk, crude oil was 88%. The separation of water efficiency was increased with increased water content and salt content. In Basrah crude oil, the separation rate was 84% at a dose of salt of 3% (30000) ppm and at zero% of salt, the separation was70.7%. In Kirkuk crude oil, the separation rate was equal 86.2% at a dose of salt equal 3% (30000) ppm, and at zero% of salt, the separation 80%.